The effect of mapping instructional materials on EFL learners with different types of materials - Eny Syatriana; Erwin Akib (Center for Humanities and Innovation Studies, 2019)
The present study examined the effect of mapping Instructional Materials on EFL learners of different types of materials, and the participant learned a different kind of book content, design, and layout of instructional materials. Also, it describes need analysis and creates a model of instructional materials through in-depth discussion among teachers of secondary schools. Data of the study were collected from six English teachers and students of three classes at three different secondary schools in Makassar, South Sulawesi, Indonesia. This study provided critical, meaningful data collection to support what English teacher perception about the design book. Pretest and posttest design were administered to see the effectiveness of the mapping, practicing, and using strategy. Questionnaires were administered to see the teachers and students’ perception toward the instructional materials. It was found that mapping instructional, practicing, and using strategy is effective in improving the English achievement; instructional materials with different strategies improve the English achievement of the students.